Integration Hydroponic Aquaculture Systems for Optimizing Catfish Growth Management with Arduino - Lawrence Adi Supriyono; A Andhika; Amalia Shifa Aldila; Prasetyo Hartanto (Jurnal Informatika Ekonomi Bisnis, 2024)
Modern agriculture faces significant challenges such as limited land and declining soil fertility. The integration of hydroponic systems with aquaculture, particularly catfish farming, offers an innovative solution to enhance agricultural efficiency and productivity. This study explores the integration of hydroponic systems with aquaculture for the simultaneous cultivation of plants and catfish in a controlled environment. The research utilizes Arduino technology for monitoring temperature, pH, and water turbidity, which are essential for the health of fish and plants. The research method used is Research and Development (R&D), involving the following steps: (1) Identifying potential problems, (2) Data collection, (3) Product design, (4) Design validation, (5) Design revision, and (6) Product testing. The results indicate that integrating hydroponic systems with Arduino technology improves the efficiency of monitoring and managing the cultivation environment, positively impacting plant and catfish growth. The implementation of this system shows an increase in plant nutrient content and better fish health. And then, this research significantly contributes to the development of sustainable agriculture and global food security through the adoption of innovative technology.